2014
DOI: 10.1055/s-0034-1387937
|View full text |Cite
|
Sign up to set email alerts
|

Pitfalls in the Surgical Management of Undifferentiated Sarcoma of the Liver and Benefits of Preoperative Chemotherapy

Abstract: USL presents with painful mixed cystic and solid liver mass. If misdiagnosed and mistreated (enucleation or unroofing), the usual good outcome of this malignancy could be impaired. Preoperative chemotherapy is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 12 publications
4
19
0
Order By: Relevance
“…A systematic review also showed that out of 14 patients (10 children and 4 adults) undergoing LT for UESL, 3 died [6]. Several other case reports and case series have also demonstrated the ability to achieve long-term survival for UESL with chemotherapy and either primary or salvage LT [12,14,26,37,38]. These findings validate the role of LT in the management of unresectable UESL.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…A systematic review also showed that out of 14 patients (10 children and 4 adults) undergoing LT for UESL, 3 died [6]. Several other case reports and case series have also demonstrated the ability to achieve long-term survival for UESL with chemotherapy and either primary or salvage LT [12,14,26,37,38]. These findings validate the role of LT in the management of unresectable UESL.…”
Section: Discussionmentioning
confidence: 78%
“…The clinical manifestations (abdominal pain, fever, anorexia) and the radiographic characteristics (solid and cystic components) are nonspecific, and thus UESL may pose a significant diagnostic challenge that can lead to a delay in appropriate management [3][4][5][6][7][8][9]. Although historically treatment was limited to surgical resection and overall survival (OS) was poor [1], the combination of surgical treatment and chemotherapy recently has led to improved OS [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The initial diagnosis of hydatid cyst may lead to the treatment delay, which was the case in three of our patients. Due to the cystic nature of some UESL, percutaneous biopsy may not always provide representative tissue and may be inconclusive 13,31 . Wildhaber et al.…”
Section: Discussionmentioning
confidence: 99%
“…European hospitals prefer VAC regimen or chemotherapy with a modified VAC backbone, but in China, we tend to use chemotherapy regimen (vincristin, cisplatin, cyclophosphamide and adriamycin) [24-29]. Merli et al [27] treated 13 undifferentiated liver sarcoma patients with surgery and postoperative chemotherapy according to the European protocol (7 patients with neoadjuvant chemotherapy). A review of the literature found 26 patients who were treated with VAC or VAC-based chemotherapy.…”
Section: Discussionmentioning
confidence: 99%